The non- -existent wall? The problem of describing Muranów - Beata Przymuszała (Przestrzenie Teorii)
The article presents the problem of recovering the memory of the Warsaw district of Muranów, the site of the WW2 ghetto in recent literature. Referring to one of the first works devoted to this subject (Jarosław Marek Rymkiewicz’s Umschlagplatz), the author reveals subsequent changes in the treatment Jacek Leociak, Beata Chomątowska and Elżbieta Janicka’s of the issue in their books. Indicating the oscillation between remembrance and forgetting about the ghetto, the authors adopt different perspectives to touch upon the ambiguous presence of the area's former inhabitants in the consciousness of today’s Varsovians. Their ways of focusing attention on this question may be termed a commemorative perspective, focused on the psychology of space and critical discourse. Though signaling the problem differently, the authors are united in emphasising the problems related to the Polish memory of the Warsaw ghetto.